Electronic pot lifter / Muhamad Hishamuddin Omar, Muhammad Nurafiq Mohd Khir and Jamri Muhamad - Omar, Muhamad Hishamuddin; Mohd Khir, Muhammad Nurafiq; Muhamad, Jamri (2013)
Nowadays, there are many work in this life is used a big force to solve it. Therefore, there are many technology have been created to make life being easier and practical. Because of that, this useful device which called “Electronic Pot Lifter” is created. This device technology is included in home category, but it also can be used in industry. The purpose of this project is to avoid the risk of getting back pain, especially for the older people and people with disabilities. This project is used to lift and move pots from one place to another place in a flat surface. In addition, this project uses three transwheels to move. The circuit of this project is divided into two, namely motor driver and controller. The motor driver circuit is used to control the movement of the wheels and gripper. A wireless PS2 controller is used to transmit signals to control the movement of the device. The device can lift up to ten kilogram pots. The device is able to grip and lift the pots from one place to another. Besides, it also has the ability to move forward, back, right, left, clockwise rotation, counterclockwise rotation, 30 °, 150 °, 210 ° and 330 °. Hopefully, the device would be useful to people with disabilities and the older people.